2018
DOI: 10.1016/j.jbankfin.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Time-series momentum in nearly 100 years of stock returns

Abstract: We document strong time-series momentum effects in individual stocks in the US markets from 1927 to 2017. Time-series momentum is not specific to sub-periods, firm sizes, formation-and holding-period lengths, or geographic markets. The effects persist after controlling for standard risk factors. Time-series momentum effects are conditional on the market state, the information discreteness of the constituent stocks and investor sentiment. We propose two alternative implementations, revised time-series momentum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 51 publications
(54 reference statements)
6
21
1
Order By: Relevance
“…Both strategies perform superior returns in the short window (12 months' formation and one month holding period) than the long window (12 months' formation and 12 months holding period). Consistent with the findings of Lim et al (2018), absolute momentum strategies generate superior returns than relative momentum strategies (in all cases). Absolute momentum payoffs remain significant in longer time frames signalling that unlike relative momentum strategies, these strategies do not reverse in the long run.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Both strategies perform superior returns in the short window (12 months' formation and one month holding period) than the long window (12 months' formation and 12 months holding period). Consistent with the findings of Lim et al (2018), absolute momentum strategies generate superior returns than relative momentum strategies (in all cases). Absolute momentum payoffs remain significant in longer time frames signalling that unlike relative momentum strategies, these strategies do not reverse in the long run.…”
Section: Discussionsupporting
confidence: 82%
“…They reported that absolute momentum strategies perform better than relative momentum strategies and "time-varying net long position" is the main source behind this superiority. Lim, Wang and Yao (2018) proved that absolute momentum effect is pervasive as they proved the efficacy of time-series momentum strategies across multiple geographical markets and sub-periods.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Also related to this area of research is time-series momentum, first proposed by Moskowitz, Ooi, and Pedersen (2012) where the previous 12-month return of an asset positively predicts future returns. 1 This finding has been strongly supported in the literature by Asness, Moskowitz, and Pedersen (2013), Georgopoulou and Wang (2017), Lim, Wang, and Yao (2018) and Hurst, Ooi, and Pedersen (2017). The literature on momentum crashes (Daniel and Moskowitz 2016) is also potentially relevant to our work although it largely deals with cross-sectional rather than time-series momentum.…”
Section: The Tendency For Prices To Trendsupporting
confidence: 62%
“…A significant body of additional research finds that the momentum strategy is profitable in several other markets outside the United States [5] A related stream of research focuses on time series momentum of individual stocks, including Moskowitz et al (2012) and Lim et al 2018; Wang et al (2018). The momentum strategy has also proved successful when applied to mutual funds, especially prior to the ETF era.…”
Section: Review Of Literature On Momentum Investment Strategiesmentioning
confidence: 99%